Strategi Komunikasi Persuasif Iklan Layanan Masyarakati Tentang Edukasi Melaksanakan Protokol Kesehatan Pada Masa Pandemi Covid-19 - I Nyoman Miyarta Yasa (Universitas Bumigora, 2021)
The Covid-19 pandemic has been going on for a year and has claimed a lot of casualties, and until now positive cases have continued to increase to close to a thousand positive cases per day. To prevent transmission of this disease and reduce positive cases, the government through the Ministry of Health has made various educational efforts to the public in order to follow and comply with health protocols during the Covid-19 pandemic. While the purpose of this research is to find out how persuasive communication of PSAs in its efforts to educate the public through visual works in the form of banners, billboards and videos. The research method used is a qualitative descriptive case study, through data collection procedures in direct interviews with several respondents and spread questions in the form of questionnaires distributed on social media. From the analysis of research data, it was found that the behavior of the target audience towards PSAs was not very good, where some informants did not care about the education and persuasiveness of PSAs and most only cared about PSAs which contained sanctions if they did not follow government recommendations. the weakness is that the information on PSA advertisements is often less attractive, and tends to be monotonous and less maintenance-wise. Persuasive communication theory is Simulated Disinterest, which states that through this persuasion technique, persuader attempts to suppress feelings of anxiety and the attitude of forcing targets to follow their wishes. This theory is used in the making of public service advertisements in Figure 5. and this persuasive technique is thought to be able to attract attention and make the public willing to carry out an invitation from the government.